2022
DOI: 10.5194/tc-16-3071-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modelling glacier mass balance and climate sensitivity in the context of sparse observations: application to Saskatchewan Glacier, western Canada

Abstract: Abstract. Glacier mass balance models are needed at sites with scarce long-term observations to reconstruct past glacier mass balance and assess its sensitivity to future climate change. In this study, North American Regional Reanalysis (NARR) data were used to force a physically based, distributed glacier mass balance model of Saskatchewan Glacier for the historical period 1979–2016 and assess its sensitivity to climate change. A 2-year record (2014–2016) from an on-glacier automatic weather station (AWS) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…However, they require a larger number of input variables, including incoming shortwave and longwave radiation, temperature, relative humidity, wind speed, and precipitation. SEB models of various complexity have been applied to individual glaciers worldwide, including several glaciers in western Canada (e.g., Ebrahimi and Marshall, 2016;Fitzpatrick et al, 2017;Marshall and Miller, 2020;Kinnard et al, 2022), showing good resemblance between modeled and observed melt, as long as the SEB models are forced by on-glacier meteorological observations. The caveat with these models, however, is that the on-glacier measurements of all SEB components are sparse in space (fewer than 100 sites worldwide and only a handful in western Canada) and of short duration (over one or two melt seasons on average).…”
Section: Introductionmentioning
confidence: 99%
“…However, they require a larger number of input variables, including incoming shortwave and longwave radiation, temperature, relative humidity, wind speed, and precipitation. SEB models of various complexity have been applied to individual glaciers worldwide, including several glaciers in western Canada (e.g., Ebrahimi and Marshall, 2016;Fitzpatrick et al, 2017;Marshall and Miller, 2020;Kinnard et al, 2022), showing good resemblance between modeled and observed melt, as long as the SEB models are forced by on-glacier meteorological observations. The caveat with these models, however, is that the on-glacier measurements of all SEB components are sparse in space (fewer than 100 sites worldwide and only a handful in western Canada) and of short duration (over one or two melt seasons on average).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the glaciological method provides the seasonal and annual surface mass balance, the time period associated with these mass-balance quantities are important – for example, any amount of melt after the end of summer survey is not included in the glaciological mass balance (Huss and others, 2009). Since the geodetic method does not provide estimates of interannual variability, numerical models (including simple temperature index models and physically based surface energy and mass-balance models) are valuable tools that are often used to simulate the seasonal and annual glacier mass balances and to test the sensitivity of glaciers to climate change (Oerlemans and Hoogendoorn, 1989; Oerlemans, 1997; Anderson and others, 2010; Arndt and others, 2021; Kinnard and others, 2022). However, numerical models rely on high-quality climate data, which can be challenging to obtain in some glaciated regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerical models rely on high-quality climate data, which can be challenging to obtain in some glaciated regions. The uncertainties and limitations inherent to each method suggest that comprehensive monitoring strategies include a combination of methods, such as glaciological observations, periodic geodetic surveys and modelled mass-balance estimates (Machguth and others, 2006; Mölg and others, 2008; Huss and others, 2009; Thibert and Vincent, 2009; Elagina and others, 2021; Kinnard and others, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the physical processes that govern the energy and mass balances and climatic response of mountain permafrost and glaciers are known, model-based projections of their future behaviour are subject to large uncertainty. This is because the observational datasets required for model calibration and validation are particularly scarce for these summit areas, where model inputs and results are often poorly constrained and extrapolated, in the absence of direct observations (Charbonneau et al, 1981;Machguth et al, 2008;Carturan et al, 2012a;Zolles et al, 2019;Kinnard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%